Summer Mortality Syndrome Affecting Cultured European Seabass at Kafrelsheikh Province, Egypt - Ali, Nadia Gabr; El-Nokrashy, Asmaa Mahmoud; Gouda, Mofeed Yousef; Aboyadak, Ibrahim Mohamed (Frontiers in Marine Science, 2021)
The present work aimed to investigate the causes of summer mortality syndrome affecting cultured European seabass (Dicentrarchus labrax) by examining physiochemical farm water characteristics, isolation, and identification of recovered bacterial pathogens from diseased fish studying the effect of water temperature on stress biomarkers and disease severity. Studied water parameters were normal except ammonia and dissolved oxygen was higher and lower than the standard value. Sixty-two bacterial isolates were recovered from moribund fish and identified as 31 Vibrio fluvialis, 23 Pseudomonas aeruginosa and 8 Staphylococcus aureus isolates. The calculated LD50 of V. fluvialis, P. aeruginosa and S. aureus for D. labrax fingerlings were 4.67 × 107, 2.37 × 106 and 1.38 × 107, respectively. There was a direct correlation between water temperature and mortality rate of fish challenged with V. fluvialis as the mortality rate was 44.44, 50, 66.66, and 83.33% for fish maintained at 27, 30, 33, and 36°C. Plasma cortisol, superoxide dismutase, catalase and malondialdehyde significantly increased when the water temperature exceeded 30°C. The experimentally infected fish showed similar clinical signs and postmortem lesions of naturally diseased fish with no boundary between different pathogens. Antibiogram test indicated that florfenicol was the most effective antibiotic against all the recovered bacterial isolates while all isolates resisted sulfamethoxazole-trimethoprim. Massive degenerative changes observed in the hepatopancreas, posterior kidney and gill tissues of experimentally infected fish.